Dinacookies.Co / Adlina Ashiqin Hasbullah - Hasbullah, Adlina Ashiqin (2021)
Dinacookies.Co is homemade chocolate chip cookies that establish in 2021. The objective of establishing this business to of course to make money and at the same time to challenge ourselves to venture into business. At the same time, dinacookies.co also produce this product to make all the customers happy when they eat the cookies. It is great when we become an expert in social media to promote our product. By using social media such as Facebook to promote our products, it could help us to expand our business and make more people aware of our product. Dinacookies.Co is targeting their customers from ranges kids to adults. This is because the observation is shown that these generations are loving to eat cookies. However, there are persons personally don’t like to eat sweets food. Therefore, we do some initiative to produce a cookie with less sugar to makes our customers happy and accept our product. we are determined to further expand our business in the future. we are very grateful to the customers who always support us to advance this business.